(untitled) (Conference on English Language Teaching, 2023)
This article aims to determine the importance of linguistics knowledge in language teaching. Linguistics is needed in language because it can help the teachers to explain the English components and the structures to the students. Every language has a system of linguistics rules that can be learned in terms of phonology morphology, syntax, and semantics. In teaching English, it must be combined to another field such as psychology, education science, bilingualism, and also language teaching. Generally, the aim of teaching English for the students is to be able use the language fluently and precisely both in spoken or written form. This paper used the method of reflection literature (library research). From the discussion, it concluded that a language teacher as an educator, coach, advisor is a Linguist practitioner who masters both the student’s language and the foreign language, he teaches in all its aspects, and understands the basic principles of teaching English using method that make easier understanding for the students.